Identifikasi Penanganan Kembali Produk Elektronik Rumah Tangga - Herdiani, Leni; Rohimat, R. Ismet; Nurwathi, Nurwathi; Munandar, Ahmad (Metris: Jurnal Sains dan Teknologi, 2019)
Reverse logistics is an item management activity that is no longer used by consumers or goods in the form of return from partners in the supply chain to be returned to the origin, because the product is unfunctional properly or the function of the item is not needed. Home appliances products within a certain period of time, these products must be replaced because they cannot technically function properly. The process of producing, using, and disposing of electronic products has an impact on the environment of the earth and the universe. If electronic waste is left without a policy to process it, there will be a buildup of electronic waste everywhere and will burden the environment. While this electronic product waste still contains economic value that can still be utilized. Therefore it is necessary to identify electronic waste handling activities, namely those that have material flow characteristics from the customer to the producer (reverse logistics), so as to provide added value.